2002
DOI: 10.1007/s00221-001-0913-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a dynamic-dominance hypothesis of handedness

Abstract: Handedness is a prominent behavioral phenomenon that emerges from asymmetrical neural organization of human motor systems. However, the aspects of motor performance that correspond to handedness remain largely undetermined. A recent study examining interlimb differences in coordination of reaching demonstrated dominant arm advantages in controlling limb segment inertial dynamics (Sainburg and Kalakanis 2000). Based on these findings, I now propose the dynamic-dominance hypothesis, which states that the essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

53
358
17
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(465 citation statements)
references
References 129 publications
53
358
17
14
Order By: Relevance
“…Previous studies indicated that the dominant arm shows a benefit in controlling the initial movement direction while the non-dominant arm is more proficient in controlling the final posture (Sainburg, 2002;Sainburg & Kalakanis, 2000). Relating these results to the results of our study, it may be accepted that basically the dominant aspect of movement control of the respective arm can be affected by the intervention.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies indicated that the dominant arm shows a benefit in controlling the initial movement direction while the non-dominant arm is more proficient in controlling the final posture (Sainburg, 2002;Sainburg & Kalakanis, 2000). Relating these results to the results of our study, it may be accepted that basically the dominant aspect of movement control of the respective arm can be affected by the intervention.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, the tendency of the dominant hand to overestimate finger forces of the non-dominant hand may indicate that the CNS simply favors the use of a command efferent signal in bimanual tasks. Thus, our findings support the dynamic dominance model of handedness (Sainburg 2002). …”
Section: Handedness Effect On Finger Force Perception In Contralaterasupporting
confidence: 87%
“…That is, directional information of the reaching movement only transferred from the left to the right arm, whereas positional information only transferred from the right to the left arm (i.e., the right and the left arms benefited from initial training with the opposite arm only in terms of initial direction and final accuracy control, respectively). They also demonstrated later (Wang and Sainburg 2006) that the two types of information transfer in opposite directions in left-handers, thus supporting the idea that the dominant and nondominant, as opposed to the left and right, limb/hemisphere systems are specialized in controlling dynamic features of movement and final limb posture, respectively (Sainburg 2002). With regard to interlimb transfer of dynamic adaptation, a number of studies have investigated the pattern of dynamic transfer and demonstrated that the pattern of interlimb transfer following dynamic adaptation is somewhat different from that following visuomotor adaptation: directional information transfers only from the right to the left arm of right-handers, and not vice versa (Criscimagna-Hemminger et al 2003;Galea et al 2007;Wang and Sainburg 2004).…”
mentioning
confidence: 63%